What are the factors associated with rural-urban inequality in under-5 deaths in low- and middle-income countries? A Fairlie decomposition analysis. - Adeniyi Francis Fagbamigbe; Taiwo Akinyode Obembe; Oyewale Mayowa Morakinyo (PLOS Global Public Health)
Background The retention of under-5 mortality (U5M) in various ramifications has dire policy implications. The varying impacts of this inequality is very important and has been researched in many rural-urban settings. In spite of many studies that have examined rural-urban inequalities, very little has been researched with respect to low middle-income countries. In this study, we utilized an innovative statistical method to examine and explain the socio-economic determinants and rural-urban differences of mortality in some selected low- and middle-income (LMIC) countries. Methods Using secondary data from the Demographic Health Survey (DHS), we utilized a Fairlie decomposition analysis to enumerate the differences amongst under-5 populations across 59 low-middle income countries in four continents. Death of any child within 0 - 59 months of life was our dependent variable while some selected individual and neighborhood factors constituted the explanatory variables. Results Study findings revealed significant pro-rural and pro-non-rural inequities across the 59 countries. Pro-rural inequities were more commonly found in the African regions. Except for the Maldives, pro-non-rural inequities were largely associated in the remaining four continents. Some factors, unemployed status, ever married or single status, female household head, insurance cover, unimproved water sources, clean fuel were associated with a higher risk of Under-5 mortality. Conclusion The results from this study are pertinent to health system reforms needed to tackle the menace of under-5 mortalities in LMICs and worldwide. Consolidation of existing maternal and child health programs supported by a resolute and firm re-evaluation of political will considerably help to control the surge of U5MR in the countries studied.